2017
DOI: 10.1111/os.12331
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Thoracic Ossification of Posterior Longitudinal Ligament with Posterior Circumferential Decompression

Abstract: Treatment with posterior transpedicular osteotomy and circumferential decompression was found to be safe, effective, reliable, and technically feasible, and keeping the thoracic cavity intact avoids many shortcomings of anterior surgery and results in a satisfactory spinal decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
11
2
Order By: Relevance
“…The cases enrolled in this study were patients who were diagnosed with OPLL in thoracic spine from August 2015 to June 2020 in our hospital. The inclusion criteria included: (1) Age ≥ 18 years old; (2) The surgery plan was a simple posterior approach to transarticular osteotomy and circumferential decompression; (3) The cases underwent complete preoperative CT examination to determine the type of OPLL and whether there was ossi cation of the ligamentum avum (OLF); (4) The surgery was done by the same team. The exclusion criteria included: (1) Age 18 years old; (2) Patients with congenital or acquired deformities of thoracic spine, such as congenital thoracic scoliosis, ankylosing spondylitis, and kyphosis secondary to spinal tuberculosis; (3) Thoracic infectious diseases; (4) Primary or metastatic spinal tumors; (5) Previous history of thoracic surgery.…”
Section: Methods Patient Screening and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cases enrolled in this study were patients who were diagnosed with OPLL in thoracic spine from August 2015 to June 2020 in our hospital. The inclusion criteria included: (1) Age ≥ 18 years old; (2) The surgery plan was a simple posterior approach to transarticular osteotomy and circumferential decompression; (3) The cases underwent complete preoperative CT examination to determine the type of OPLL and whether there was ossi cation of the ligamentum avum (OLF); (4) The surgery was done by the same team. The exclusion criteria included: (1) Age 18 years old; (2) Patients with congenital or acquired deformities of thoracic spine, such as congenital thoracic scoliosis, ankylosing spondylitis, and kyphosis secondary to spinal tuberculosis; (3) Thoracic infectious diseases; (4) Primary or metastatic spinal tumors; (5) Previous history of thoracic surgery.…”
Section: Methods Patient Screening and Selectionmentioning
confidence: 99%
“…(2) Once the patient has symptoms of low intracranial pressure such as headache, the bed tail would be raised for 10 cm, or the trendelenburg position would be adopted to alleviate the symptoms. (3) Water and electrolyte should be taken on a regular basis to strengthen nutritional support. For patients with low intracranial pressure symptoms, intravenous infusion of concentrated sodium chloride was conducted to alleviate the symptoms.…”
Section: Diagnostic Criteria For Csflmentioning
confidence: 99%
“…The occurrence of ossification of the posterior longitudinal ligament (OPLL) in the thoracic spine is about 0.8% (1), which is lower than that of OPLL in the cervical spine. However, due to the limited activity of thoracic spine as well as poor compensatory effect of thoracic spinal cord, bone compression often requires static compression (2,3). Therefore, once clinical symptoms of OPLL occur in the thoracic spine, they progress rapidly and can cause severe spinal cord injury or even paraplegia in a short time.…”
Section: Introductionmentioning
confidence: 99%
“…Circumferential decompression (CD) has been widely used due to its effectiveness in removing the compression around the spinal cord even postoperative complication rate was relative higher. Many scholars have confirmed that the posterior approach can achieve satisfactory surgical results (2,3). Nevertheless, the operation is highly difficult and can result in many complications, with cerebrospinal fluid leakage (CSFL) being one of the most common (4).…”
Section: Introductionmentioning
confidence: 99%
“…It is considered one of the most challenging spinal surgeries, mainly owing to its unique anatomy and pathophysiological factors. The main disadvantages of this operation can be summarized as follows: i) The incidence of thoracic natural kyphosis may limit the positive effect of spinal cord retreat following posterior decompression; ii) the thoracic spinal cord is characterized by relatively low blood supply, leading to spinal cord ischemia and consequently spinal cord injury; and iii) OPLL with tight adhesion to the dural sac increases the difficulty of removing the ossified ligament and increases the risk of intraoperative spinal cord injury (3)(4)(5)(6)(7)(8). Therefore, patients with T-OPLL that proceed to surgical treatment often result in unsatisfactory prognosis (9,10).…”
Section: Introductionmentioning
confidence: 99%